2019
DOI: 10.1590/2177-9465-ean-2018-0292
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms related to inhalation of surgical smoke in the nursing team

Abstract: Objective: To compare the prevalence of signs and symptoms related to inhalation of surgical smoke among surgical technologists and non-surgical technologists nursing professionals. Method: A cross-sectional study with 46 professionals from a university hospital. To evaluate the prevalence, an instrument with signs/symptoms related to the inhalation of electrocautery smoke was used. To verify the comparison between the prevalence of signs/symptoms, the Fisher’s exact test was performed. Results: Higher preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…Indeed, a recent study was conducted with surgical workers to compare the prevalence of signs and symptoms related to inhalation of surgical smoke among surgical technologists and non-surgical technologists nursing professionals. As a result, a statistical significance was found as regards the presence of eye irritation (p = 0.02), nasal mucosa and oral cavity irritation (p = 0.03) and headache (p = 0.04), when comparing surgical and non-surgical technologists nursing professionals (35) .…”
Section: Polycyclic Aromatic Hydrocarbons and Development Of Respiratmentioning
confidence: 92%
“…Indeed, a recent study was conducted with surgical workers to compare the prevalence of signs and symptoms related to inhalation of surgical smoke among surgical technologists and non-surgical technologists nursing professionals. As a result, a statistical significance was found as regards the presence of eye irritation (p = 0.02), nasal mucosa and oral cavity irritation (p = 0.03) and headache (p = 0.04), when comparing surgical and non-surgical technologists nursing professionals (35) .…”
Section: Polycyclic Aromatic Hydrocarbons and Development Of Respiratmentioning
confidence: 92%
“…In a typical procedure, a chief surgeon, a surgeon assistant, a circulating nurse, an anesthesiologist, one or two surgical technicians and even a medical device representative may be present as well as others depending on the complexity of the surgical case. Saito, et al [1] asserted in their cross-sectional study of 46 subjects, 10 of which were nurses, and 36 technologists and nurse assistants, all working in the surgical center of Londrina State University in the state of Paraná, Brazil, that nurses remained in the operating room intermittently. Surgical technologists and non-surgical technologists nursing professionals remained in the room from receipt of the patient in the OR to transfer of the patient to the postanesthesia care unit.…”
Section: The Operating Room-staff Positionmentioning
confidence: 99%
“…This technology was developed by Harvey Cushing and William T Bovie. Saito, et al [1] described its use as common due to the many advantages such as the reduction in surgical time and intraoperative bleeding, as well as improvement of visibility of the surgical field. As a result of temperatures of more than 100°C (212°F), products generated from use of an electrocautery device are water vapor and surgical smoke (SS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical smoke contains toxic gaseous compounds (i.e., hydrogen cyanide, toluene, benzene, and carbon monoxide) that can be hazardous to the human body (Fencl, 2017). Saito et al (2019) reported that OR personnel experienced side effects from exposure to hazardous surgical smoke; specifically, that continuous exposure can cause anemia, dermatitis, headaches, inflammation of the eyes and mucous membranes, and respiratory diseases (e.g., asthma, emphysema, and chronic bronchitis; Okoshi et al, 2015;York & Autry, 2018). Another study confirmed that prolonged exposure to surgical smoke may have deleterious effects on OR personnel's health status (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%